Trends in Intake and Outcome Data From U.S. Animal Shelters From 2016 to 2020 - Rodriguez, Jeffrey R.; Davis, Jon; Hill, Samantha; Wolf, Peter J.; Hawes, Sloane M.; Morris, Kevin N. (Frontiers in Veterinary Science, 2022)
In this retrospective, exploratory study, intake, and outcome data were compiled from 1,373 U.S. animal shelters for which such data were reported consistently across a five-year study period (2016–2020). Linear regression analysis was used to examine the five-year trends and the impacts of the first year of the COVID-19 pandemic (2020) on the overall trends in intake and outcomes in U.S. animal shelters. Results of the analysis reveal that total intake and euthanasia for both dogs and cats significantly decreased over the study period. The adoption, return-to-owner, return-to-field, and transfer (for cats) categories as a percentage of intake all showed significant increases. Live-release rates as a function of total intakes and of total outcomes for both dogs and cats showed significant increases over the study period. The findings from this study address a critical gap in the field by summarizing emerging trends at the national level in how cats and dogs are being served in U.S. animal shelters.